(untitled) (Communications in Computational Physics, 2006)
The nearly analytic discrete method (NADM) is a perturbation method originally proposed by Yang et al. (2003) [26] for acoustic and elastic waves in elastic media. This method is based on a truncated Taylor series expansion and interpolation approximations and it can suppress effectively numerical dispersions caused by the discretizating the wave equations when too-coarse grids are used. In the present work, we apply the NADM to simulating acoustic and elastic wave propagations in 2D porous media. Our method enables wave propagation to be simulated in 2D porous isotropic and anisotropic media. Numerical experiments show that the error of the NADM for the porous case is less than those of the conventional finite-difference method (FDM) and the so-called Lax-Wendroff correction (LWC) schemes. The three-component seismic wave fields in the 2D porous isotropic medium are simulated and compared with those obtained by using the LWC method and exact solutions. Several characteristics of wave propagating in porous anisotropic media, computed by the NADM, are also reported in this study. Promising numerical results illustrate that the NADM provides a useful tool for large-scale porous problems and it can suppress effectively numerical dispersions.